β-Catenin Directs Nuclear Factor-κB p65 Output via CREB-Binding Protein/p300 in Human Airway Smooth Muscle - Koopmans, Tim; Eilers, Roos; Menzen, Mark; Halayko, Andrew; Gosens, Reinoud (Frontiers in Immunology, 2017)
β-catenin is a multifunctional protein that apart from its role in proliferative and differentiation events, also acts upon inflammatory processes, mainly via interaction with nuclear factor-κB (NF-κB). However, there is still controversy as to whether β-catenin facilitates or represses NF-κB output. Insights into the molecular mechanisms underlying the interaction between β-catenin and NF-κB have highlighted the co-factors CBP and p300 as important candidates. Here, we hypothesized that the interaction of β-catenin with CBP/p300 directs NF-κB output. Using human airway smooth muscle cells, we found that β-catenin is essential in IL-1β-mediated expression of IL-6 by promoting nuclear translocation of the p65 subunit of NF-κB. These effects were independent from WNT pathway activation or other factors that promote β-catenin signaling. In the nucleus, inhibition of either the CBP- or p300-β-catenin interaction could regulate NF-κB output, by enhancing (CBP inhibition) or inhibiting (p300 inhibition) IL-1β-induced expression of IL-6, respectively. Acetylation of p65 by p300 likely underlies these events, as inhibition of the p300-β-catenin interaction diminished levels of acetylated p65 at lysine 310, thereby reducing p65 transcriptional activity. In conclusion, β-catenin is a critical component of NF-κB-mediated inflammation in human airway smooth muscle, affecting transcriptional output by interacting with the nuclear co-factors CBP and p300. Targeting β-catenin may be an alternative strategy to treat airway inflammation in patients with airway disease, such as asthma.